Factors related to perinatal mortality in public hospital in Huanuco - Dámaso-Mata, Bernardo C. (2014)
Objective. To determine the preconceptional, pregnancy, delivery and product risk factors related to perinatal mortality in the Hermilio Valdizan Hospital of Huanuco during 2007-2008 period. Materials and methods. A case series; retrospective and analytical design. The target population was all born in the hospital, registered in the clinical history, Perinatal Information System and CLAP. The perinatal mortality was response variable. The exposure variables were divided into preconceptional, pregnancy, delivery and product factors. Exclusion criteria were incomplete information in clinical history, Perinatal Computer System or CLAP. Bivariate analysis was performed with chi2, Fisher and Mann-Whitney U-test. Multivariate analysis was by multiple logistic regressions. Results. The perinatal mortality rate was 16,5 [IC95 % (12,3; 21,7)] per 1 000 live births (LB). Educational attainment (illiterate) [OR 2,89 (IC95 % 1,28; 6,54) p = 0,011], type of delivery (cesarean) [OR 0,48 (IC95 % 0,24; 0,96) p = 0,038], birth weight (< 2500 g) [OR 3,05 (IC95 % 1,19; 7,83) p = 0,020], gestational age (< 37 weeks) [OR 3,19 (IC95 % (1,26; 8,08) p = 0,014], Apgar (< 8 score) [OR 13,74 (IC95 % 5,21; 36,25) p = 0,000] and diagnosis of hyaline membrane [OR 21,01 (IC95 % 5,21; 84,68) p = 0,000] were independently associated with perinatal mortality. Conclusions. Educational attainment (illiterate), birth weight (< 2500 g), gestational age (< 37 weeks), Apgar (< 8 score) and diagnosis of hyaline membrane were independently related factors with perinatal mortality. Cesarean delivery was a protective factor.